PEMERIKSAAN Escherichia coli PADA AIR BAK WUDHLU 10 MASJID DI KECAMATAN TLOGOSARI SEMARANG - Ratih Haribi; Khoirul Yusron (JURNAL KESEHATAN, 2010)
Water tanks for wudhlu at the mosque in Tlogosari Semarang, comes from wells, rarely drained through pipes and used without a shower or faucet. Ablution basin water users, directly dipping the body into the tuband rinse with water from the tub ablution.Escherichia coli was the coliform group bacteria, which are used for indicators of water pollution by the stool, because the bacteria are normal flora of the colon, where stool in the process. Thus if the germs get onthe water, means water contaminated by stool. E. coli can cause diarrhea in its host, if high population immunity and depressed conditions.Based on the above, it is necessary to study the bacteriology of water washing basin, which aim to know the germ E. coli in it, so it can be given information about sanitation and the provision of proper ablutionwater for the community.When the study began in March 2008 to complete. Place of research conducted at the Laboratory of Microbiology, University of Muhammadiyah Semarang, Jl. Wonodri Sendang No. 2A Semarang.Samples were taken in total population at l0 mosques, on 10, 15 and March 20,2008, using a sterile bottle brown, henceforth conducted l00x dilution, were cultured in media Mac Concey (370C incubation, for 24hours, gram staining, biochemical tests, and repeat 2 timesExamination results show that in all there ablution basin E. coli and the population of most meetings occur at the mosque 2, 5 and 6 because of the distance ablution basin less than 2 feet from the septic tank. Insamples from the mosque 3 and 9 populations of E. coli meetings, because the distance was only 5 feet from septic tanks. Besides E. coli bacteria there are also other means such as Enterobacter sp., Pseudomonas sp, Citrobacter and Proteus vulgaris diwersus ablution basin Distance from septic tanks that are too close to allow the bacteria contamination stool into the washing tub through the water that seeps into the groundKey words: coliform, the host, normal flora